Can Active Investment Managers Beat The Market? A Risk-Adjusted Return & Three Factor Model Study On Active And Passive Portfolios In Indonesia - Pramudito, Yohannes Samuel Satrio; Rokhim, Rofikoh (UNIVERSITAS PAKUAN, 2024)
Is your portfolio safe in the hands of the investment manager you have chosen? This research goes into depth on the comparison of returns and risks in active portfolios managed by investment managers with active strategies, and passive portfolios managed with passive strategies or mimicking the composition of an index. The sample for this research are stock/equity mutual funds data spanning within the period of 2019-2023 and also several stock indexes and selected stock index ETFs spanning a similar period. Data was obtained from various historical data portals ranging from the OJK mutual fund website to the Refinitiv Eikon financial data portal. By using fundamental ratios from the Capital Asset Pricing Model (CAPM) such as the Sharpe, Treynor and Jensen ratios, this research aims to find a significant relationship between portfolio performance with the portfolio types. To add robustness, this research also uses the Fama French Three-Factor Model method to then identify the existence of systematic and unsystematic risk within the research samples. The sample tested includes 209 active stock/equity mutual fund portfolios and 10 stock indexes, some of which are represented by index ETF proxies. The significance of the results are then tested with Z-test and chi-squared test.